Research trends of the neuroimaging in aphasia: A bibliometric analysis and visualization analysis from 2004 to 2021 - Huang, Jiaqin; Cao, Yun; Zhang, Danli; Lei, Xiaojing; Chang, Jingling (Frontiers in Human Neuroscience, 2022)
Objectives: To review the current research status of the neuroimaging of aphasia through CiteSpace, and reveal the hotspots and frontiers of research in this field. Methods: We searched articles related to the neuroimaging research on aphasia since Web of Science (WOS) database construction and extracted the data. CiteSpace was used for the country/institution analysis, journal analysis, discipline analysis, burst keyword analysis and cited-reference cluster analysis. Results: Of the studies retrieved from WOS, 2922 studies that related to the neuroimaging of aphasia were screened and finally included 2799 articles for research. The United States of America and University of California San Francisco were the main countries and institutions in this field. Brain had the highest impact factor in both published and cited journals. Through the discipline and topic analysis of this field, the most common category was Neurosciences & Neurology. The keyword with the strongest citation strength was ‘functional connectivity’, and the recent burst keywords were ‘functional connectivity’ and ‘network’. The cocitation network showed seven clusters greater than 100. Among the top 5 clusters, the most recently formed cluster, Cluster #2 (progressive supranuclear palsy), had an average year of 2017. The literature in the top 5 clusters mainly focused on 3 aspects, specifically, the discovery of language processing models, injury and recovery mechanisms of poststroke aphasia (PSA), and diagnosis of primary progressive aphasia (PPA) variants. Conclusions: The results of this bibliometric study revealed the following three research hotspots in the neuroimaging of aphasia: clarifying the connotation of the most recognized language processing model, the dual-stream model, exploring the injury mechanism based on the dual-stream model and the recovery mechanism involving the left and right hemispheres of PSA, and determining the diagnostic criteria for PPA variants. A major research trend is to combine new neuroimaging technology, such as PET tracer technology, to realize the visual presentation of disease-specific proteins to improve the pathological diagnostic criteria of PPA variants. Accordingly, a visualized analysis of literature that uses CiteSpace provides a more rapid, repeatable and flexible method, which is more conducive to capturing research hotspots and emerging trends.